Prognostic role of the pretreatment systemic immune-inflammation index in patients with glioma: A meta-analysis - Zhang, Sunhuan; Ni, Qunqin (Frontiers in Neurology, 2023)
Background: The systemic Immune-Inflammation Index (SII) has been recognized as the indicator which reflects the status of immune responses. SII is related to prognostic outcome of many malignancies, whereas its role in gliomas is controversial. For patients with glioma, we therefore conducted a meta-analysis to determine if SII has a prognostic value. Methods: Studies relevant to this topic were searched through October 16, 2022 in several databases. In glioma patients, relations of SII levels with patient prognosis were analyzed based on hazard ratios (HRs) as well as corresponding 95% confidence intervals (CIs). Moreover, subgroup analysis was conducted to examine possible heterogeneity source. Results: There were eight articles involving 1,426 cases enrolled into the present meta-analysis. The increased SII level predicted dismal overall survival (OS) (HR=1.81, 95%CI=1.55–2.12, p<0.001) of glioma cases. Furthermore, an increased SII level also predicted the prognosis of progression-free survival (PFS) (HR=1.87, 95%CI=1.44–2.43, p<0.001) in gliomas. An increased SII was significantly associated with Ki-67 index ≥30% (OR=1.72, 95%CI=1.10–2.69, p=0.017). However, a high SII was not correlated with gender (OR=1.05, 95%CI=0.78–1.41, p=0.734), KPS score (OR=0.64, 95%CI=0.17–2.37, p=0.505), or symptom duration (OR 1.22, 95% CI 0.37–4.06, p=0.745). Conclusion: There was a significant relation of an increased SII level with poor OS and PFS of glioma cases. Moreover, glioma patients with high SII have positive relationship with Ki-67 ≥30%.